Analyzing the impact of risk profile on financial performance in banks: Moderating effect of good corporate governance - Maulydia, Dewi Sri; Setiawati, Ririt Iriani Sri (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
The restrictions on economic activity during the COVID-19 pandemic harmed banking stability in Indonesia. This is reflected in the decline in banks' financial performance in 2020 due to high losses on various risk profiles. These risks do not only occur under certain conditions, such as a pandemic, but are also inherent in the bank's business activities. Therefore, this study analyzes the impact of credit risk, operational risk, and liquidity risk on bank financial performance in 2019-2024, involving GCG as a moderating variable. The purpose of this analysis is to provide an overview of the quality of risk management in commercial banks in Indonesia. The object of this research is commercial banks listed on the IDX. The research sample consisted of 15 banks, selected through purposive sampling. The data were analyzed using panel data models and moderated regression (MRA). The results showed that credit risk and operational risk had a negative effect, while liquidity risk did not affect bank financial performance. GCG weakens the negative relationship between operational risk and financial performance, but does not moderate the relationship between credit risk and liquidity risk. The findings suggest that the risk management of commercial banks in Indonesia is suboptimal, particularly in terms of credit risk and operational risk. Tighter supervision by GCG is also necessary to mitigate the adverse effects of risk.